Pituitary adenoma: important genetic factors and clinical diagnostic issues - G. Juknytė; E. Karinauskė; R. Liutkevičienė (Neurologijos seminarai)
Pituitary adenoma (PA) is a benign tumor of parenchymal cells in the adenohypophysis. Clinically significant PA occurs in 1 in 1064 of the population. Invasive PAs, pituitary carcinomas, are aggressive and can spread from sella turcica to other tissues. PA invasiveness and tumor-caused metabolic disorders can also be fatal, as almost every human organ and tissue is directly or indirectly affected by hormones secreted by the anterior or posterior pituitary gland. Most PAs occur spontaneously and their origin is not well known. It is thought to be a disease of multifactorial etiology, the occurrence of which is influenced by genetic factors, hormonal stimulation, and growth factors. PA can be inherited in an autosomal dominant manner. Recently, many new genetic alterations have been identified that make people predisposed to pituitary adenomas. Attempts are also being made to find new molecular diagnostic and prognostic targets that would contribute to more effective treatment of pituitary adenomas. Since the development of pituitary adenomas can be significantly influenced by epigenetic changes in pituitary cells, there is currently an increasing focus on the study of epigenetic mechanisms such as DNA methylation, histone modifications, and micro-RNA studies. Analysis of mRNA expression is also performed to assess the decrease or increase in gene expression in the case of pathology. All of these studies are aimed at finding new molecular markers for the development of targets for the treatment of pituitary adenomas. Therefore, in this article, we review the genetic issues of pituitary adenoma.